External debt, growth and investment for developing countries : some evidence for the debt overhang hypothesis - Turan, Taner (2022)
We investigate the effect of total, public, and private external debt stocks on the growth rate and also on total, government, and private investment by using data for a large sample of developing countries. We find a significant and negative growth effect of total external debt stock, lending evidence for the debt overhang argument. Moreover, our results importantly indicate that external debt lowers growth only in countries with ethnically fractionalized and ineffective governments. Furthermore, our empirical findings don’t support the existence of a non-linear or threshold relationship between external debt and growth. Similar to the growth effects of external debt, the significantly and negatively estimated coefficients on the three measures of external debt stocks imply that external debt reduces investment, again providing a robust evidence for the debt overhang argument. Finally, our estimations show that private investment level is more sensitive to the government external debt than the private external debt.